Unmet needs of chronic hepatitis C in the era of direct-acting antiviral therapy - Chung-Feng Huang; Ming-Lung Yu (Clinical and Molecular Hepatology, 2020)
The treatment of chronic hepatitis C (CHC) has been revolutionized in an era of all-oral direct-acting antivirals (DAAs) since 2014. Satisfactory treatment efficacy and tolerability can be provided by novel DAAs. Nevertheless, there are still some unmet needs and emerging issues in the treatment of CHC in the DAA era. Certain hard-to-cure populations are prone to have inferior treatment responses, including patients with severe liver decompensation, active hepatocellular carcinoma (HCC), and hepatitis C virus (HCV) genotype 3 (HCV-3) infection and those who experience multiple DAA treatment failures. Hepatitis B virus (HBV) reactivation during and after DAA treatment has raised concern regarding the use of prophylactic antivirals against HBV throughout DAA treatment. However, the standard strategy for the use of prophylactic antivirals is not uniform across regional guidelines. In the post-sustained virological response (SVR) period, HCC still occurs in a substantial proportion of patients. Due to the relatively short follow-up period, the net benefit of the achievement of an SVR by DAAs in the reduction of extrahepatic manifestations has not yet been determined. Attention must also be paid to HCV reinfection, particularly in high-risk populations. The most critical and unmet need for HCV elimination is the large gap in the HCV care cascade at the population level. To accomplish the World Health Organization (WHO)’s goal for HCV elimination by 2030, the expansion of access to HCV care requires a continuous effort to overcome practical and political challenges.